Histórias do fogo: recordações familiares, racismo e o tempo do cativeiro sertanejo (Ágora Journal, 2020)
This article analyzes memories of the sertanejo captivity among quilombola families in Piemonte da Chapada Diamantina, Bahia. The richness of these reports is in expressing the views of descendants of enslaved people about the experience of their ancestors, in view of the specifics of slavery in the hinterlands. The collective memory of black rural communities reveals stories that remained in families after 132 years of formal emancipation. The post-abolition in the backlands is the result of a silenced slave past that was confused with free rural work that was not (or badly) hired under the sign of racism.